The Belt and Road Initiative: an analysis about China’s global projection in the 21st century - Kotz, Ricardo Lopes (2020)
This article examines the geo-economic role of China’s foreign direct investments in the implementation of the Belt and Road Initiative (BRI), the main foreign policy concept of the Xi Jinping administration. Two timeframes are proposed in order to analyze China’s international projection: 40 years and 20 years. These time frames encompass the process of reform and opening up, starting in 1978, going through the global projection of Chinese investments with the Going Global strategy and which currently results in the New Silk Road, or Belt and Road Initiative. The main results of the article suggest that even though BRI was launched as a plan for building infrastructure across Eurasia, it has now become a broad concept for understanding China’s position in the international system, especially in conducting its relations with emerging countries. The time frames analyzed show a continuity in China’s political and strategic trajectory aiming at obtaining its main state objective: the continuity of its economic development. The theoretical contribution of geo-economics is important, in this article, in order to understand the implementation and consolidation of BRI through the issuance of foreign direct investments.